(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2022)
Cu2ZnSnS4 (CZTS) thin films are fabricated on glass substrates using the spray pyrolysis method with different concentrations of Sn content were studied in this research work. All the CZTS thin films are fabricated at substrate temperature 200°C to minimize the formation of secondary phases. Here, we show how the variation in Sn content concentration influences the optical and structural properties of the CZTS thin films. The XRD patterns reveal that the concentration of Sn content has to be optimized to minimize the formation of secondary phases for a fixed substrate temperature. In turn, the band gap of the CZTS films is highly influenced by the formation of secondary phases. We have found that the films prepared from the precursor solution with 1.8 mM concentration of Sn content have the best crystal structure and an optical band gap of 1.55 eV. The CZTS thin films also have good carrier concentrations ranging from 4.2×1019 to 22.9×1020 cm-3. Bangladesh J. Sci. Ind. Res. 57(1), 1-6, 2022